Patient and partner experiences with Obstructive Sleep Apnoea and Mandibular Advancement Devices: A qualitative analysis - KHASAWNEH, LINA (Trinity College Dublin. School of Dental Sciences. Discipline of Dental Science, 2018)
Aim of the study: To elucidate the experience of patients and partners who are living with Obstructive Sleep Apnoea (OSA) and undergoing Mandibular Advancement Device (MAD) therapy and examine the factors that influence adherance and acceptance of treatment. The influence of the partners? role and level of engagement in treatment was also explored. Materials and Methods: Semi-structured in-depth interview qualitative research methodology was used. In this study two groups of patients were interviewed. The first group was for patients who have worn MADs only. The second group was for patients who were using MADs following failure to adhere to CPAP therapy. Partners of OSA patients were also interviewed to highlight their experience with their partners? condition and treatment of OSA. Results: A total of fifteen participants were interviewed in this research. Ten of them were patients who had been diagnosed with Obstructive Sleep Apnoea (OSA) and five of their bed partners. Of the ten patients interviewed, five of them used mandibular advancement devices (MADs) following failure to adhere to Continuous Positive Airway Pressure (CPAP) treatment. The impact of OSA on patients? and partners? lives, and their perspectives on the condition were explored. Patients? experience with the diagnosis and treatment with OSA was highlighted. For patients who failed to adhere to CPAP treatment technical and psychological factors, and side effects of the treatment were explored. Facilitators and barriers to MAD treatment were analysed. Patients also reflected on their experiences with the services provided, how services could be improved, and the possible role of support groups in treatment. Finally, the partners? roles in diagnosis, treatment and on-going management of OSA were highlighted. Conclusion: OSA is a shared problem between patients and partners; it affects the quality of life of patients and is an impairment to patients? work, social life, and the ability to perform daily functions. Patients diagnosed with OSA associated it with a number of psychological factors such as association with old age, depression, and impairment. Psychological factors such as locus of control, health attitudes and influence of significant others should be identified at the beginning of treatment to predict adherence to the prescribed treatment. OSA patients described that they would like to be actively involved in their own treatment. Partners? instigated the process for patients to seek medical advice, and the partner?s role were not gender specific. They can have an active role in treatment of OSA. An array of roles were described; active sensitivity, passive adaptation, and direct confrontational approaches. For some partners cultural influences and classic gender roles influenced their perceived roles. OSA should be treated as a chronic condition that requires active intervention from patients paired with regular check visits and repeat sleep studies to assess patients? progress. Management of OSA should focus on a wholesome approach that involves incorporating healthy sleeping habits, getting patients and partners actively involved in treatment, adherence to prescribed treatment, and regular maintenance and follow up.
APPROVED
Keywords: Sleep Apnoea, Qualitative Study, Partner, Mandibular Advancement Device, Continuous Positive Airway Pressure